Negative Even Grade mKdV Hierarchy and its Soliton Solutions - Gomes, J. F. [UNESP]; de Melo, G. R. [UNESP]; Starvaggi Franca, G. [UNESP]; Zimerman, Abraham Hirsz [UNESP] (Iop Publishing Ltd, 2011)
In this paper we discuss the algebraic construction of the mKdV hierarchy in terms of an affine Lie algebra (s) over capl(2). An interesting novelty araises from the negative even grade sector of the affine algebra leading to nonlinear integro-differential equations admiting non-trivial vacuum configuration. These solitons solutions are constructed systematically from generalization of the dressing method based on non zero vacua. The sub-hierarchies admiting such class of solutions are classified.